Evaluasi Kebijakan Layanan Kartu Tanda Penduduk Elektronik (KTP-El) Sebagai Bentuk Penerapan Identitas Berbasis Single Identity Number di Kabupaten Lampung Utara - Nia Janati (e-JKPP, 2015)
Electronic identity card program is one of the government programs relating to the administration of population the purpose electronic ID card program according to Law No. 24 Year 2013 on the amandement of the Act No. 23 Year 2006 concerning Population Administration Population Administration was later every citizen of Indonesia or the public will only have one ID Card with a valid Citizen Identification Number, Accuracy database of Indonesia’s population, as well as an electronic ID Card is also designed to be faster making process.Riset problem in this research is how achievement targets and policy target program Electronic Identity Card, How do the result of the implementation of the procedures and mechanism Electronic Identity Card program policies and what are the resources used in the implementation of the Electronic Identity Card program policy in the North Lampung regency. To know that in this case the researchers took the theory of public policy evaluation of Wayne Parson about formative evaluation which can be seen from reached targets and objectives, the consistency of the mechanism of implementation procedures and resources used. The method in this study used a qualitative approach, data collection techniques done with participatory observation, interview and documentatition.The result showed that the application of an electronic ID card service policy in North Lampung regency is not running effectively this can be seen in terms of targets and objectives have not been achieved, terms of implementation mechanism of the electronic ID card program in North Lampung regency has not been implemented consistenly in accordance with the procedures set and terms of human resources and fund is in the implementation of the electronic ID card program in North Lampung regency is still inadequate.